Production and productivity of pole and liner catching based at the Fishing Port Ocean in Bitung: Production and productivity of pole and liner catching based at the Fishing Port Ocean in Bitung - Mamarimbing, Yudistira Josua; Kaparang, Frangky Erens; Labaro, Ivor Lembondorong (Jurnal Ilmiah Platax, 2023)
Skipjack tuna is classified as an important pelagic fishery resource and is one of the export commodities so that production needs to be continuously increased by maintaining the sustainability of these fish resources. This study aims to determine the development of production and productivity of the pole and liner vessels observed and to determine the length-weight relationship of the catches of the pole and liner vessels observed at the Bitung Ocean Fishing Port (PPS). In general, the production and productivity of pole and liners based at the Samudera Bitung Fishing Port increased from November 2021 to December 2021 and then decreased again in January 2022, so that they were declared unproductive. Pole and liner catches that are landed at the Bitung Ocean Fishing Port in the period November 2021 - January 2022 tend to get the same results with the size caught, namely 29-64 cm, with a positive allometric growth pattern. Keywords : Production and Productivity, Growth Patterns, Pole and Liner Abstrak Ikan cakalang tergolong sumberdaya perikanan pelagis penting dan merupakan salah satu komoditi ekspor sehingga produksinya perlu terus ditingkatkan dengan menjaga kelestarian sumberdaya ikan tersebut. Penelitian ini bertujuan untuk mengetahui perkembangan produksi dan produktivitas dari kapal pole and liner yang diamati dan mengetahui hubungan panjang-berat hasil tangkapan kapal pole and liner yang diamati di Pelabuhan Perikanan Samudera (PPS) Bitung. Secara umum produksi dan produktivitas pole and liner yang berpangkalan di Pelabuhan Perikanan Samudera Bitung mengalami kenaikan dari bulan November 2021 ke bulan Desember 2021 dan selanjutnya mengalami penurunan kembali pada bulan Januari 2022, sehingga dinyatakan tidak produktif. Hasil tangkapan pole and liner yang didaratakan di Pelabuhan Perikanan Samudera Bitung pada periode November 2021 – Januari 2022 cenderung mendapatkan hasil yang sama dengan ukuran yang tertangkap yaitu 29-64 cm, dengan pola pertumbuhan bersifat alometrik positif. Kata Kunci : Produksi dan Produktivitas, Pola Pertumbuhan, Pole and Liner